ʼPhags pa ʼJig rten dbaṅ phyug gi rnam sprul rim byon gyi ʼkhruṅs rabs deb ther nor buʼi ʼphreṅ ba (Sku-sger Yig-tshaṅ, 1977)
Biographies of the successive embodiments of Avalokiteśvara as the Dalai Lamas of Tibet: from Dge-ʼdun-grub, 1391-1474, to Thub-bstan-rgya-mtsho, 1876-1933.